Trade facilitation - WTO law and its revision to facilitate global trade in goods - Bolhöfer, Carolin Eve (2007)
Describes what trade facilitation entails and how it demonstrates its impact. Looks at the current WTO trade facilitation negotiations and also multilateral trade agreements. Examines some of the Members' proposals submitted to the WTO Secretariat.